Factors associated with homelessness and its medical issues among urban Malaysians : a qualitative research / Nurul Mahfuzah Ahmad Yani ... [et al.] - Ahmad Yani, Nurul Mahfuzah; Zahari, Nur Zakirah; Abu Samah, Nur Fatini Haziqah; Mohamed Azahar, Muhammad Ammar Faidhi; Yasin, Siti Munira; Ahmad Saman, Mohd Shahril; Mohd Noor, Nor Aini (Faculty of Medicine, 2016)
Introduction: Homelessness continues to exist in our country even though we hear of various initiatives that have been put in place to solve this ongoing issue. The objectives of this study are, first, to explore factors that lead to homelessness, second, to determine the associated medical conditions and third, to shed light on the views of homeless individuals regarding their future perspectives. Methods: This study employed the use of a qualitative research method in analysing the experiences of 24 homeless individuals. It will detail the causes that have led to the respondents' homelessness and their future plans. Results: From the research conducted, it was found that the factors that lead to homelessness are family disorganization, job loss and underemployment, not having a place to call home and attitude problems. The future plans of the 24 respondents can be divided into several broad themes - finding a job, finding their families, finding a better shelter home and seeking for knowledge, while some had no obvious plans. Most of the 24 individuals had no knowledge of their own medical conditions. Conclusions: Initiatives from people with authority or organizations dedicated to working on issues of homelessness are not enough to prevent this condition from occurring. People who are homeless must themselves be willing to change their attitudes while family members must care and be responsible for their own families. Health awareness is very important and the occurrence of communicable diseases such as tuberculosis can be prevented if more attention is given to health.